2021
DOI: 10.31616/asj.2020.0084
|View full text |Cite
|
Sign up to set email alerts
|

Is Older Age a Contraindication for Single-Level Transforaminal Lumbar Interbody Fusion?

Abstract: This study's primary objective was to compare the clinico-radiological outcomes and incidence of perioperative complications of transforaminal lumbar interbody fusion (TLIF) at lower lumbar levels for elderly and younger patients. The secondary objective was to evaluate the effect of age on clinical outcomes and patient satisfaction in the two groups. Overview of Literature: The lumbar interbody fusion surgery in elder age has been reported to produce a higher complication rate and suboptimal results. Literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…17 Two similar studies also demonstrated good clinical outcomes following MI-TLIF irrespective of age. 13,14 These findings of comparable outcomes across age groups emphasize the advantage of the use of minimally invasive techniques for lumbar fusion in the elderly. Previously, Glassman et al had demonstrated that following open TLIF, older patients may have worse outcomes compared to younger patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…17 Two similar studies also demonstrated good clinical outcomes following MI-TLIF irrespective of age. 13,14 These findings of comparable outcomes across age groups emphasize the advantage of the use of minimally invasive techniques for lumbar fusion in the elderly. Previously, Glassman et al had demonstrated that following open TLIF, older patients may have worse outcomes compared to younger patients.…”
Section: Discussionmentioning
confidence: 76%
“…Transforaminal lumbar interbody fusion (TLIF) is regarded as a workhorse technique for the treatment of degenerative conditions of the lumbar spine. 13 Although various studies have been previously conducted to assess the outcomes of minimally invasive TLIF (MI-TLIF) in the elderly, [13][14][15][16][17][18] only a few have reported minimum clinically important difference (MCID) achievement rates, 17,18 and none have reported the time taken to achieve MCID, return to activities, and discontinue opioids postoperatively. Therefore, the purpose of this comparative study was to fill this gap in the literature by assessing the MCID achievement, return to activities, and opioid discontinuation, in addition to analyzing the improvement in patientreported outcome measures (PROMs), fusion rates, and complication/reoperation rates in patients ≥ 70 years old following MI-TLIF.…”
mentioning
confidence: 99%
“…The sagittal plane must be adjusted for fusion surgery to be successful, and even elderly patients aged over 65 and very senior patients aged over 80 can have successful operations provided the sagittal plane is balanced thereafter. Gained is decrease the chance of falls following surgery [28,29,53,54]. Recently, single-or biport endoscopic surgery and minimally invasive screw [59].…”
Section: Principles Of Spinal Stenosis Surgerymentioning
confidence: 99%
“…We have read the article “ Is older age a contraindication for single-level transforaminal lumbar interbody fusion?” by Patel et al [ 1 ] with great interest and appreciate the authors for their informative work. This article was extensively discussed in our departmental journal club meeting recently and few doubts were raised which seek solution and redressal before establishing safety and utility of transforaminal lumbar interbody fusion (TLIF) amongst the elderly.…”
mentioning
confidence: 99%